Different Modes of Hydrogen Peroxide Action During Seed Germination - Wojtyla, Łukasz; Lechowska, Katarzyna; Kubala, Szymon; Garnczarska, Małgorzata (Frontiers in Plant Science, 2016)
Hydrogen peroxide was initially recognized as a toxic molecule that causes damage at different levels of cell organization and thus losses in cell viability. From the 1990s, the role of hydrogen peroxide as a signaling molecule in plants has also been discussed. The beneficial role of H2O2 as a central hub integrating signaling network in response to biotic and abiotic stress and during developmental processes is now well established. Seed germination is the most pivotal phase of the plant life cycle, affecting plant growth and productivity. The function of hydrogen peroxide in seed germination and seed aging has been illustrated in numerous studies; however, the exact role of this molecule remains unknown. This review evaluates evidence that shows that H2O2 functions as a signaling molecule in seed physiology in accordance with the known biology and biochemistry of H2O2. The importance of crosstalk between hydrogen peroxide and a number of signaling molecules, including plant phytohormones such as abscisic acid, gibberellins and ethylene and reactive molecules such as nitric oxide and hydrogen sulfide acting on cell communication and signaling during seed germination, is highlighted. The current study also focuses on the detrimental effects of H2O2 on seed biology, i.e., seed aging that leads to a loss of germination efficiency. The dual nature of hydrogen peroxide as a toxic molecule on one hand and as a signal molecule on the other is made possible through the precise spatial and temporal control of its production and degradation. Levels of hydrogen peroxide in germinating seeds and young seedlings can be modulated via pre-sowing seed priming/conditioning. This rather simple method is shown to be a valuable tool for improving seed quality and for enhancing seed stress tolerance during post-priming germination. In this review, we outline how seed priming/conditioning affects the integrative role of hydrogen peroxide in seed germination and aging.